Experimental investigation of dual fuel (gasoline-natural gas) in lean burn ICE - Seyyed Kazem Yekani; Mehrdad Sarabi; Mahdi Nami Khalilehdeh (International Journal of Thermofluids, 2025)
Investigating the performance and emission indices of spark ignition engines in our society is a critical issue. This importance arises from the high performance requirements and the need to achieve the highest level of efficiency from existing spark ignition engines. Another significant factor in selecting spark ignition engines and fuel types is environmental pollution. In fact, the performance and emission indices determine how we utilize spark ignition engines and fuel combinations within society.Previous research has experimentally studied the performance and emission indices of a combined spark ignition engine operating in lean burn mode. In this study, five fuel combinations with varying mass ratios of gasoline and natural gas mixtures were utilized. The equivalence ratio selected for lean burn was 0.9. To ensure the experimental data are applicable for industrial use, a safe knock range (%KC < 5) was applied to all data. In all data sets from this experimental test, the basis for selecting the optimal ignition advance was a high performance index.The results of this experimental study indicate a decrease in the average indicated mean effective pressure (IMEPAV) and torque when adding natural gas to gasoline. However, it should be noted that combustion becomes more stable with an increasing proportion of natural gas. Regarding the pollutants emitted from the exhaust of the combustion engine, it is observed that as the mass percentage of natural gas in the dual fuel increases, the emissions of CO and CO2 decrease, while NOx emissions increase. The findings suggest that combustion mixture systems can be more effective in controlling greenhouse gas emissions compared to pure gasoline.